2022
DOI: 10.1093/jogss/ogac042
|View full text |Cite
|
Sign up to set email alerts
|

Cyberattacks, Psychological Distress, and Military Escalation: An Internal Meta-Analysis

Abstract: To what extent can cyberattacks wreak havoc and terrorize modern society? Until now, this question has revolved around the potential of cyber operations to cause physical destruction or other material harm. In this paper, we propose a broader interpretation. We submit that assessing cyber-threats through the prism of physical destruction has obscured the human dimension of the threat. Instead, we propose calculating the gravity of cyberattacks by measuring psychological distress. This approach recognizes that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 74 publications
0
13
0
Order By: Relevance
“…My exploration of the dynamics involved in the strategic targeting of state-sponsored cyber economic espionage offers a valuable springboard into exploring the psychological and societal impacts of cyber-attacks. For instance, Shandler, Gross & Canetti (2023) underscore the significant psychological distress caused by cyber-attacks, equating it to the impact of conventional political violence. The linkage between the tactical espionage activities discussed in this article and the psychological fallout explored by Shandler, Gross & Canetti (2023) opens an avenue for contemplating the ethical and humanitarian considerations of cyber espionage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…My exploration of the dynamics involved in the strategic targeting of state-sponsored cyber economic espionage offers a valuable springboard into exploring the psychological and societal impacts of cyber-attacks. For instance, Shandler, Gross & Canetti (2023) underscore the significant psychological distress caused by cyber-attacks, equating it to the impact of conventional political violence. The linkage between the tactical espionage activities discussed in this article and the psychological fallout explored by Shandler, Gross & Canetti (2023) opens an avenue for contemplating the ethical and humanitarian considerations of cyber espionage.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Shandler, Gross & Canetti (2023) underscore the significant psychological distress caused by cyber-attacks, equating it to the impact of conventional political violence. The linkage between the tactical espionage activities discussed in this article and the psychological fallout explored by Shandler, Gross & Canetti (2023) opens an avenue for contemplating the ethical and humanitarian considerations of cyber espionage.…”
Section: Discussionmentioning
confidence: 99%
“…Insofar as cyberterrorism is just a methodological subset of terrorism, the public may search for characteristics it associates with conventional terrorism. Yet while cyberterrorism is unquestionably related, research has shown that it is substantively different from conventional terrorism in its practice and effects ( Backhaus et al 2020 ; Shandler, Snider, and Canetti 2022 ; Shandler and Gomez 2022 ; Shandler et al, 2023 ). We therefore hypothesize that there will be several distinguishing predictive features that are unique to cyberterrorism.…”
Section: When Do Cyberattacks Become Cyberterrorism In the Eyes Of Th...mentioning
confidence: 99%
“…These findings may explain why, although catastrophic attacks have not happened, most United States citizens still perceive cyberattacks to be the greatest national security threat, even above nuclear weapons (Vise ´, 2023). Consequently, even if cyber-attacks themselves remain low in intensity, public threat perception may still increase the risk of escalation by pressuring governments to retaliate (Jardine and Shandler, 2024;Shandler et al, 2022Shandler et al, , 2023. Moreover, how cyber-attacks are perceived can shape public opinion concerning security policy, such as attitudes towards surveillance (Arsenault et al, forthcoming).…”
Section: Introductionmentioning
confidence: 99%